Proton triggered circularly polarized luminescence in orthogonal- and co-assemblies of chiral gelators with achiral perylene bisimide. Issue 44 (18th May 2018) - Han, Dongxue; Han, Jianlei; Huo, Shengwei; Qu, Zuoming; Jiao, Tifeng; Liu, Minghua; Duan, Pengfei
Abstract : Acid–base exposure switched circularly polarized luminescence was achieved in a coassembled gel which is composed of a chiral gelator and achiral perylene bisimide. Abstract : The orthogonal- or co-assembly of achiral perylene bisimide (PBI) with chiral gelators can be regulated by solvents. While the coassembly leads to the formation of chiroptical nanofibers through chirality transfer, the orthogonal assemblies could not. Moreover, protonation on the coassembled nanofibers could light up the circularly polarized luminescence (CPL).